(untitled) (Veterinary Science, 2017)
Lawsonia intracellularis is an obligate intracellular bacterium that causes proliferative enteropathy in pigs. The bacterium do not growth in standard mediums, its develop in cellular cultures; under low oxygen tension nevertheless is expensive and complex. It is a difficult diagnosis disease where de IgY technology might be useful in the development of lower cost and more efficacy assays. Throughout the immunization of hens with the strain of the bacterium it is possible to obtain specific IgY. In the present work, it was evaluated the capacity of yield specific IgY against Lawsonia intracellularis by immunizing Brown Nick hens with a commercial live attenuated vaccine. Thereafter, IgY was isolated by precipitation – PEG methodology and the extract were analysed by polyacrylamide gel electrophoresis (SDS-PAGE). The indirect immunofluorescence confirmed the presence of IgY specific against Lawsonia intracellularis establishing that the commercial vaccine could be utilised as antigen, instead of the strain of bacterium, as a source of antigen to induce specific immunoglobulins